First record of Lindenia tetraphylla (Vander Linden, 1825) and rediscovery of Orthetrum nitidinerve (Selys, 1841) in Sicily (Insecta: Odonata) - Surdo, Salvatore (Fragmenta entomologica, 2017)
The first Sicilian record of Lindenia tetraphylla and a new regional record of Orthetrum nitidinerve, species not recorded since 1975 in mainland Sicily, are here reported. All individuals of L. tetraphylla and O. nitidinerve were observed in the same site in the province of Trapani.